2003
DOI: 10.1176/appi.ps.54.8.1119
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Successful Efforts to Reduce the Use of Seclusion and Restraint at a Public Psychiatric Hospital

Abstract: The results of this analysis underscore the importance of clinical and administrative priorities in efforts to reduce the use of seclusion and restraint in public psychiatric hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 15 publications
1
99
1
Order By: Relevance
“…When these and other interventions introduced at the hospital were examined together statistically, the revised case review procedure was the only significant predictor of reduced restraint/seclusion (18). The procedures lowered the threshold for review to include lower risk patients and ensured that reviews and modifications to treatment occurred more quickly.…”
Section: Multi-faceted Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…When these and other interventions introduced at the hospital were examined together statistically, the revised case review procedure was the only significant predictor of reduced restraint/seclusion (18). The procedures lowered the threshold for review to include lower risk patients and ensured that reviews and modifications to treatment occurred more quickly.…”
Section: Multi-faceted Interventionsmentioning
confidence: 99%
“…In one, a decrease in hospital beds over a decade was accompanied by an increase in staff numbers (30). Two studies from the same state psychiatric hospital found statistically significant correlations between higher staffpatient ratios and lower use of seclusion and restraint (15,18). One study reported the introduction of a staff roster system to enable nurses to work with a variety of patients in order to reduce burnout associated with continuous work with acutely unwell patients (31).…”
Section: Staffingmentioning
confidence: 99%
See 1 more Smart Citation
“…Staffing levels are a long standing and an important concern in some forensic psychiatric hospitals (Arboleda-Fl orez 2006; Livingston 2006;Way et al 1990). Increasing staff-to-patient ratios, and investing in staff education on alternative behavioural management techniques, decreased violent incidents, and SR use; attention to staff-to-patient ratio may help some forensic regimes reduce their SR incidence (Donat 2003;Donovan et al 2003;Morrison et al 2002). Like clinicians have a parens patriae duty towards their patients and clients, so do organisations towards their staff members.…”
Section: Ecological Factorsmentioning
confidence: 99%
“…Administrative and staffing changes, specifically increases in the ratio of staff to service users, have also been shown to reduce the use of seclusion and restraint. Donat [106][107][108] found that changes at these levels reduced use by up to 75%.…”
Section: Coercion In Services and Treatmentmentioning
confidence: 99%